2017
DOI: 10.3168/jds.2017-13110
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR coupled with propidium monoazide for the detection of viable Cronobacter sakazakii, Bacillus cereus, and Salmonella spp. in milk and milk products

Abstract: Cronobacter sakazakii, Bacillus cereus, and Salmonella spp. are common food-borne pathogens. The aim of this study was to develop a sensitive, specific, and rapid method for the simultaneous detection of these 3 pathogens in milk and milk products. Three specific primers were designed based on ompA, invA, and cesB of C. sakazakii, Salmonella spp. and B. cereus, respectively, for use in a multiplex PCR (mPCR). To eliminate false-positive results, cells were pretreated with propidium monoazide (PMA) for the sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Consequently, the PCR signal is strongly reduced even suppressed in membrane-compromised cells compared to intact cells. This methodology has been widely applied to detect viable bacteria (Yu et al 2017), viruses (Fongaro et al 2016), fungi (Vesper et al 2008) in food and environmental samples, and Cryptosporidium spp. oocysts and G. duodenalis cysts in water and wastewater effluents (Brescia et al 2009;Liang and Keeley 2012;Agulló-Barceló et al 2014;Alonso et al 2014;Ma et al 2016;Vande Burgt et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the PCR signal is strongly reduced even suppressed in membrane-compromised cells compared to intact cells. This methodology has been widely applied to detect viable bacteria (Yu et al 2017), viruses (Fongaro et al 2016), fungi (Vesper et al 2008) in food and environmental samples, and Cryptosporidium spp. oocysts and G. duodenalis cysts in water and wastewater effluents (Brescia et al 2009;Liang and Keeley 2012;Agulló-Barceló et al 2014;Alonso et al 2014;Ma et al 2016;Vande Burgt et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…) and milk and milk products (Yu et al . ). In the present study, this pathogen was identified in raw milk and cheese samples and our results may present a different perspective for C. sakazakii .…”
Section: Discussionmentioning
confidence: 97%
“…in vegetables, fruit and environmental samples. In addition, the presence of C. sakazakii was investigated in milk-based ingredients such as milk powder, whey powder and cheese (Heperkan et al 2017) and milk and milk products (Yu et al 2017). In the present study, this pathogen was identified in raw milk and cheese samples and our results may present a different perspective for C. sakazakii.…”
Section: Discussionmentioning
confidence: 99%
“…PMA-multiplex qPCR [55] Milk E. coli O157: H7; Salmonella spp. PMA-multiplex qPCR [56] Probiotic yogurt Bifidobacterium EMA-qPCR [57] Lactobacillus paracasei PMA-qPCR [58] Seafood Fish fillets 16S rDNA EMA-qPCR [59,60] PMA-qPCR [61] Raw seafood (oyster, scallop, shrimp, and crab)…”
Section: Gouda Cheesementioning
confidence: 99%